Effects of silver nitrate on adventitious-buds formation in mulberry leaves cultured in vitro - ZHONG Ming-qi; LOU Cheng-fu; TAN Jian-zhong; ZHOU Jing-mei; ZHANG You-zhuo (浙江大学学报. 农业与生命科学版, 2000)
The effects of AgNO3 treatment on adventitious-buds formation in mulberry leaves cultured in vitro were studied. The results showed that compared with the control, treatment with addition of AgNO3 to the culture media at the concentration of 1.0-2.0 mg·L-1 presented a stable differentiation rate of 81.3%-87.5%, substantial increase of the clustered buds rate and 5-7 days earlier initiation of adventitious-buds differentiation. It was also found that the duration of culturing leaves on the media containing AgNO3 should be no longer than 10 days, otherwise the frequency of differentiation would be reduced, and the cultures grew poorly, due to the toxic effect of Ag+.